Habits of Mind and Concept Mastery of Cell in Multimedia Virtual Class Environment: A Case of Biology Students in Lampung University - Rakhmawati, Ismi; Hasnunidah, Neni; Priadi, Median Agus (FKIP Universitas Lampung, 2019)
The ability of students to use Information and Communication Technology (ICT) is still not optimally integrated with learning. Even though most students already have gadgets, internet connections are available via campus hotspots. Based on this, learning in higher education cannot be separated from the use of computerized and online-based technology. The integration of ICT into vclass-based multimedia learning is a potential thing to develop. This vclass-based multimedia application is expected to improve habits of mind and conceptual understanding of biology cell of students. Improved learning outcomes can be demonstrated through conceptual understanding which are the ability to understand the concepts that exist in the learning material after the learning process takes place.Keywords: habits of mind, mastery of concepts, cells, virtual class. DOI: http://dx.doi.org/10.23960/jpmipa/v20i1.pp17-22